Maths

2010-02-16 7:10 am

回答 (1)

2010-02-16 7:36 am
✔ 最佳答案
(x - √3)^2 + | y - cos 30 | = 0
Since (x - √3)^2 >= 0 and | y - cos 30 | >= 0
So (x - √3)^2 = 0 and | y - cos 30 | = 0 for their sum = 0
x = √3 and y = cos 30 = √3 /2
(3xy - x^2 y^2) / (xy - 1) * (1/xy - 1)
= (3xy - x^2 y^2) / (xy - 1) * (1 - xy)/xy
= (x^2 y^2 - 3xy) / xy
= xy - 3
= √3 * √3 /2 - 3
= 3/2 - 3
= - 3/2


收錄日期: 2021-04-21 22:09:07
原文連結 [永久失效]:
https://hk.answers.yahoo.com/question/index?qid=20100215000051KK01233

檢視 Wayback Machine 備份